Organizing physical space of urban landscape based on sustainable development criteria (Case Study: 11th District of Tehran Municipality) - kermani, Amirmohsen Jabbarinejad; Shafaghi, Sirous; Beikmohammadi, Hasan (Opción, 2017)
Run down fabric has not yet been able to reconcile with the current conditions of the country’s urbanization as a complex network of relationships that have survived from previous generations despite the many changes over the past 50 years because socio-economic and political changes which has created a new spatial relationships in the run down fabric from the beginning of the century, in line with the global trend and following the developed countries in the form of modernization process which is practically opposed to its past. In line with the goal of sustainable urban development, the main goal is to address vulnerable tissues, especially the studied area as a set in which all historical and cultural values are relevant, and its physical organizing from the point of view of urban landscape is creating a healthy and pleasing environment. In order to achieve this goal, other sub-goals have been examined and proposed. It includes the study of all problematic factors that have made it inconceivable to visualize the nature of the studied urban area through field survey and photo analysis, as well as the study of regional functions and planning to transfer them from the scope as one of the main causes of creating confusion and disorder